Quality of life among Patients with Acute Coronary Syndrome in Malaysia - Soraya, Azmi; Goh, Adrian; Fong, Alan; Lawrence, Anchah (ElsevierInc., 2015)
Objectives This study’s objectives were to estimate the quality of life (QOL) of Malaysian patients with acute coronary syndrome (ACS) during admission and at 12 months, to explore the factors associated with the QOL, and to compare utility scores derived from tariffs from local and foreign populations.